Pre-excitation induced left ventricular dysfunction: A less known cause of cardiomyopathy in children - PR Bhima Shankar; Chidambaram Shanthi; Kottarathu Mammen Cherian (Wolters Kluwer Medknow Publications, 2013)
A 7-year-old boy was diagnosed to have dilated cardiomyopathy with severe left ventricular (LV) dysfunction at 1 year of age. Although well compensated, his LV function remained impaired over the follow-up years. His electrocardiogram (ECG) was initially misinterpreted as left bundle branch block. However, on follow-up, it was recognized as a pre-excited ECG. The accessory pathway causing pre-excitation was implicated as the cause of LV dysfunction and dysynchrony as the mechanism. Radiofrequency ablation was done. His LV function and dimensions improved significantly over 6 months follow up.